أسطورة مَجْلَبَة الثَرَاء في منظور تقاليد الحياة الدينية لدى طائفة من المسلمين الموالين للتقاليد الجاوية (State Islamic University (UIN) of Sunan Ampel Surabaya, 2009)
This paper deals with the problem of the visit to the sacred sites by the nominal Muslims of Java and its religious, social and cultural ramification. It argues that the dialectic expression of the visitors depends very much on the cultural setting of the sites they visit. It specifically identifies three groups of expression, abangan deles (purely nominal), putihan campuran (half-heartedly puritan) and bisnisan gak ngalor gak ngidul (inconsistent commercialists). The first group tends to be magical-emotional, the second is magical-rational, and the third is empirical-rational. Despite this difference in mythical expression, the three groups share the mythical experience. The paper goes on to say that if Islam is understood in mythical sense, it must be tolerant, adaptive, collaborative, acculturative, and transformative.